2014
DOI: 10.3389/fphy.2014.00055
|View full text |Cite
|
Sign up to set email alerts
|

CO2dissociation using the Versatile atmospheric dielectric barrier discharge experiment (VADER)

Abstract: Dissociation of CO 2 is investigated in an atmospheric pressure dielectric barrier discharge (DBD) with a simple, zero dimensional (0-D) chemical model and through experiment. The model predicts that the primary CO 2 dissociation pathway within a DBD is electron impact dissociation and electron-vibrational excitation. The relaxation kinetics following dissociation are dominated by atomic oxygen chemistry. The experiments included investigating the energy efficiencies and dissociation rates of CO 2 within a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 54 publications
4
23
0
Order By: Relevance
“…We believe that this is one of the reasons for the higher CO 2 conversion upon addition of Ar or He. A similar explanation was also recently given by Lindon et al…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…We believe that this is one of the reasons for the higher CO 2 conversion upon addition of Ar or He. A similar explanation was also recently given by Lindon et al…”
Section: Resultssupporting
confidence: 88%
“…A large number of experiments have been performed already in pure CO 2 , but also mixed with CH 4 , H 2 , or H 2 O, to form value‐added chemicals. Moreover, a few papers have reported on the mixing of CO 2 (and CH 4 ) with a rare gas, such as He or Ar . Pinhao et al investigated CO 2 /CH 4 /He mixtures in a DBD and observed that the addition of He results in a drop in the breakdown voltage and it enhances the conversion of both CO 2 and CH 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These anthropogenic activities at the same time are the main sources of CO 2 emission, which is believed to be in a strong relation to the greenhouse effect and so‐called global warming. Among the different approaches proposed nowadays for reducing the CO 2 pollution, the plasma‐based conversion of CO 2 into the valuable chemicals represents an extremely useful option . Under certain conditions, low‐temperature plasma can be an ideal environment for CO 2 conversion, which happens due to the formation of charged highly energetic species that can activate chemical reactions difficult or impossible to realize using ordinary thermal mechanisms .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we study the formation of carbonaceous solid products in pure CO 2 and CO Dielectric Barrier Discharge (DBD) systems, which represent a popular NTP approach for carbon dioxide decomposition . Interestingly, coke deposition is mostly not observed in such DBD reactors when working with CO 2 .…”
Section: Introductionmentioning
confidence: 99%